Adsorption onto ash particles and common ion effect for phosphorus recovery from urinal wastewater - Yada Pinatha (2018)
© 2017, Greater Mekong Subregion Academic and Research Network, Asian Institute of Technology. The aim of the study was to evaluate the effect of ash addition on phosphorus (P) recovery from urine through chemical processes. P recovery efficiency was improved in association with an increase of pH value. At pH 7, 9, and 11, P was recovered into solid precipitates maximally at 75%, 99%, and 99%, respectively with a P content as P crystals of about 70%, 60%, and 50%, respectively. The addition of incinerator ash led to the enhancement of P recovery via adsorption and precipitation. The behavior of P adsorption onto lignite and solid waste ashes of experiments with synthetic urine was fitted based on the Langmuir and Freundlich isotherms. Results of human urine adsorption studies found Freundlich isotherm provided a better fit for data. However adsorption capacities were much lower as compared to synthetic urine. The addition of 2.5 g·L-1lignite fly ash and solid waste fly ash into human urine having 0.09%P led to a P-containing ash that contained P about equal to the P content in commercial superphosphate fertilizer at 8.89% and 8.93%, respectively. Results therefore indicate that recoverable P from urinal wastewater can be effectively used to produce fertilizer for agricultural cultivation by common ion precipitation and adsorption processes.